2017
DOI: 10.1111/imig.12255
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Aspects of Conflict, Displacement and Peace Process in Turkey

Abstract: The peace process in Turkey, since its inception, has not paid any attention to internal displacement or its gendered aspects. This study analyses how displaced women remember the gendered aspects of displacement and perceive reconciliation and peace. The analysis, based on interviews with 42 internally displaced women, shows that changing domestic and international contexts have substantive impact on how displaced women remember their stories and the meaning they attach to their ethnic identities. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Since respondents indicated that they were not comfortable being recorded, interviews were not taped. As Celik () demonstrates, that the perspectives of women are heard is imperative to the success of sustainable peace‐ and state‐building processes. In Somaliland, women hold few elite positions and for this study it proved difficult to reach female respondents.…”
Section: Introductionmentioning
confidence: 99%
“…Since respondents indicated that they were not comfortable being recorded, interviews were not taped. As Celik () demonstrates, that the perspectives of women are heard is imperative to the success of sustainable peace‐ and state‐building processes. In Somaliland, women hold few elite positions and for this study it proved difficult to reach female respondents.…”
Section: Introductionmentioning
confidence: 99%